2014
DOI: 10.1155/2014/478983
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Suggesting That Obesity Prevention Measures May Improve Prostate Cancer Outcomes Using Data from a Prospective Randomized Trial

Abstract: Purpose. Increasing body mass index (BMI) is associated with higher risk prostate cancer (PC) at presentation. Whether increasing BMI also prompts earlier salvage androgen suppression therapy (sAST) is unknown. Materials and Methods. Between 1995 and 2001, 206 men with unfavorable risk PC were treated with radiation therapy (RT) or RT and six months of androgen suppression therapy in a randomized controlled trial (RCT). 108 sustained PSA failure; 51 received sAST for PSA approaching 10 ng/mL; 49 with BMI data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…While the role of CXCL8 has been comprehensively studied in the context of prostate cancer and other cancers 42 43 54 , CXCL1 function in cancer remains insufficiently understood. Our study links obesity-dependent CXCL1/CXCR1 gradient activation in the prostate with obesity-dependent cancer progression reported previously 22 23 24 25 26 . Analysis of the tumours of 39 patients undergoing radical prostatectomy for localized disease under our clinical protocol demonstrated that obese patients were more likely than non-obese patients to have lymph node metastases (17 versus 0%, Supplementary Fig.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…While the role of CXCL8 has been comprehensively studied in the context of prostate cancer and other cancers 42 43 54 , CXCL1 function in cancer remains insufficiently understood. Our study links obesity-dependent CXCL1/CXCR1 gradient activation in the prostate with obesity-dependent cancer progression reported previously 22 23 24 25 26 . Analysis of the tumours of 39 patients undergoing radical prostatectomy for localized disease under our clinical protocol demonstrated that obese patients were more likely than non-obese patients to have lymph node metastases (17 versus 0%, Supplementary Fig.…”
Section: Discussionsupporting
confidence: 71%
“…Increased adiposity in prostate cancer patients has been identified as a factor associated with disease aggressiveness 22 23 24 25 26 . Tumour stroma, composed of a mixture of various non-malignant cells types, has been identified as one of the drivers of cancer progression 15 18 19 51 52 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation